Foreign Direct Investment and Employment: Home Country Experience in the United States and Sweden - Magnus Blomström; Gunnar Fors; Robert E. Lipsey (The Research Institute of Industrial Economics (IUI), 1997)
We compare the relation between foreign affiliate production and parent employment in U.S. manufacturing multinationals with that in Swedish firms. U.S. multinationals appear to have allocated some of their more labor intensive operations selling in world markets to affiliates in developing countries, reducing the labor intensity in their home production. Swedish multinationals produce relatively little in developing countries and most of that has been for sale within host countries with import-substituting trade regimes. The great majority of Swedish affiliate production is in high-income countries, the U.S. and Europe, and is associated with more employment, particularly blue-collar employment, in the parent companies. The small Swedish-owned production that does take place in developing countries is also associated with more white-collar employment at home. The effects on white-collar employment within the Swedish firms have grown smaller and weaker over time.
Keywords: F23; J23; 330; Foreign direct investment; Home employment